A Significant Association Between Rhein and Diabetic Nephropathy in Animals: A Systematic Review and Meta-Analysis - Hu, Heng-Chang; Zheng, Liu-Tao; Yin, Hai-Yan; Tao, Yuan; Luo, Xiao-Qiong; Wei, Kai-Shan; Yin, Li-Ping (Frontiers in Pharmacology, 2019)
Background: Rhein is considered to have beneficial influence on diabetic nephropathy. Animal experiments suggested that the mechanisms of rhein against diabetic nephropathy may involve many processes, but the credibility of the evidence is unclear. Therefore, we conducted systematic review and meta-analysis of pre-clinical animal data to assess the current evidence for rhein effects and mechanisms in treating diabetic nephropathy. Methods: The databases of PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure, VIP information database, Wanfang Data Information Site, and Chinese Biomedical Literature were searched for this review. SYRCLE’s risk of bias tool for animal studies was applied to assess the methodological quality of studies. A meta-analysis was performed according to the Cochrane Handbook for Systematic Reviews of Interventions by using RevMan 5.3 and STATA/SE 12.0 software. This study was registered with PROSPERO, number CRD42018105220. Results: Twenty-five studies involving 537 animals were included. There was significant association of rhein with levels of blood glucose (P < 0.05), serum creatinine (Scr) (P < 0.05), urine protein (P < 0.05), kidney tubules injury index (P < 0.05), relative area of kidney collagen (P < 0.05), transforming growth factor-β1 (P < 0.05), malondialdehyde (P < 0.05), and superoxide dismutase (P < 0.05) compared with that in the control group. No significant association between rhein and endothelin (P > 0.05) was found. Subgroup analysis showed that the hypoglycemic effect of rhein on type 2 diabetic nephropathy was better than on type 1 diabetic nephropathy (P < 0.05). Conclusions: These findings suggested that rhein has beneficial effects on animal models of diabetic nephropathy, and that the mechanisms are mostly involved with ameliorating levels of TGF-β1, renal fibrosis, metabolism, and oxidative stress status. However, some factors such as possible publication bias, methodological quality, and sample size may affect the accuracy of positive findings. These limitations suggested that a cautious interpretation of the positive results of this systematic review and meta-analysis is necessary. Therefore, high methodological quality and well-reported animal experiments are needed in future research.